Market Failure Requires Aggressive Action - Nagusky, Beth (Maine Policy Review, 1991)
Secure and reasonably priced energy supplies have always been vital to the welfare of Maine's economy and its people. Maine responded to the energy shocks of the 1970s with important state policies, designed in large part to reduce dependence on foreign oil. John Flumerfelt and Richard Silkman of the State Planning Office [this issue] provide an overview of Maine's recent history of energy use and an analysis of both past and future energy policies in Maine. Beth Nagusky of the Natural Resources Council of Maine provides here an alternative perspective on energy policy.
Keywords: Market failure; energy policy